The Making of a Reform Jewish Cantor : Musical Authority, Cultural Investment - Cohen, Judah M. (Book collections on Project MUSE., 2019)
"The Making of a Reform Jewish Cantor provides an unprecedented look into the meaning of attaining musical authority among American Reform Jews at the turn of the twenty-first century. How do aspiring cantors adapt traditional musical forms to the practices of contemporary American congregations? What is the cantor's role in American Jewish religious life today? Judah M. Cohen follows cantorial students at the School of Sacred Music, Hebrew Union College, over the course of their training, as they prepare to become modern Jewish musical leaders. Opening a window on the practical, social, and cultural aspects of aspiring to musical authority, this book provides unusual insights into issues of musical tradition, identity, gender, community, and high and low musical culture."--Jacket